نظم تصنیف مقتنیات المتاحف :دراسة تحلیلیة تقییمة مقارنة - د. سمیرة خلیل محمد (المجلة الدولية لعلوم المكتبات والمعلومات)
The study examined the classification systems of museum collections forbeing one of the tools and standards in documenting museum collections, withthe aim of monitoring the attributes and characteristics of the applicableclassification systems in museums, Where the definition of the concept ofclassification of museum collections, and determine the motives and justificationswhich are paid about museums classification of their collections, With inventory ofclassification systems of museum collections through search engines, Then studywhich are available in English-language Web site in light of the basic componentsof systems classifications, namely: the main schedules, tables, index, manual,which a number of elements of evaluation included in the checklist,. It was in thisstudy the application of the field survey method, in addition to the assessmentreport method, and the data collection tools are represented in the directexamination sites classification systems understudy and available on the web, aswell as the application of checklist referred to above